Psychiatric Symptoms due to Thyroid Disease in a Female Adolescent. (4th November 2014) - Capetillo-Ventura, Nelly; Baeza, Inmaculada
Abstract : The hypothalamic-pituitary-thyroid axis is involved in the production of thyroid hormone which is needed to maintain the normal functioning of various organs and systems, including the central nervous system. This study reports a case of hypothyroidism in a fifteen-year-old female adolescent who was attended for psychiatric symptoms. This case reveals the importance of evaluating thyroid function in children and adolescents with neuropsychiatric symptoms.